Structural and dynamic insights into supra-physiological activation and allosteric modulation of a muscarinic acetylcholine receptor - Jun Xu; Qinggong Wang; Harald Hübner; Yunfei Hu; Xiaogang Niu; Haoqing Wang; Shoji Maeda; Asuka Inoue; Yuyong Tao; Peter Gmeiner; Yang Du; Changwen Jin; et al. (Nature Communications, 2023)
Here, using cryo-electron microscopy and solution NMR, the authors reveal the structural and dynamic mechanisms underlying the signaling versatility of a muscarinic receptor regulated by orthosteric and allosteric ligands.